Des mondes religieux parallèles, un espace commun? Amérindiens et musique vocale européenne sous le Régime français - Dubois, Paul-André (Études d'histoire religieuse, 2001)
This article is devoted to the question of French religious music used by Christian Indians of New France during the 17th and 18th centuries. More particularly, it examines the surprising success of this religious and artistic practice in the post-contact North American world. It appears that cultural more than geopolitical or socioeconomic factors can explain the rapid adoption of European religious songs by Indians. In my opinion, only a better understanding of the role traditionally held by singing in the Indian culture could help us identify the cultural basis on which such a success is based. From there, it becomes possible to sustain a larger reflection about Catholicism's influence among Indians during the historical period.

Archéologie sonore. Chants amérindiens - Tremblay-Matte, Cécile; Rivard, Sylvain (Éditions Trois, 2001)
Traduit l'importance historique et culturelle des chants traditionnels des dix nations amérindiennes du Québec. Certains d'entre eux sont parvenus à passer outre l'évangélisation et l'influence de la culture européenne. Textes en langue autochtone et transcription des mélodies.